2020
DOI: 10.1051/sicotj/2020042
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and translation of the Constant Murley Score into Arabic

Abstract: Introduction: Shoulder pain is a major disorder of the musculoskeletal system. To the best of our knowledge, there is no documentation of an Arabic version of the shoulder disability and pain measurements. Constant Murley Score (CMS) is one of the standard questionnaires for clinical practice and research. The aim of this research centred around the evaluation of the Arabic Constant Murley Score and subsequently assessing the reliability and validity in comparison to disabilities of the arm, shoulder, and hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The literature has reported that females suffer from ACL ruptures in females 2–4 times more than their male counterparts, however, our sample size only had 6 females in total so they were excluded from this study [ 4 , 19 ]. The authors theorize that this could be due to cultural reasons that generally discourage females from pursuing athletic careers [ 4 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The literature has reported that females suffer from ACL ruptures in females 2–4 times more than their male counterparts, however, our sample size only had 6 females in total so they were excluded from this study [ 4 , 19 ]. The authors theorize that this could be due to cultural reasons that generally discourage females from pursuing athletic careers [ 4 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is why the quadrupled hamstring tendon option has become the mainstay practice in Kuwait for anterior ACLR [3,4]. The reason being for this trend in Kuwaiti orthopedic surgical practice is that the cultural behaviors and daily living practices would be exacerbated by the BPTB related anterior knee pain should it happen [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations